Elaborating on Internet addiction and cyberchondria – relationships, direct and mediated effects - Ivanova, Eliza; Karabeliova, Sonya (Journal of Education Culture and Society, 2020)
The present paper focuses on the effects of personality traits on the levels of Internet addiction and cyberchondria and their consequent effects on well-being. For the purposes of the research, mediation analyses were carried out, clarifying the infl uence of personality traits on well-being mediated by Internet addiction, cyberchondria and anxiety aroused by online health information seeking. It was established that Neuroticism leads to decreased well-being through the mediating infl uence of health anxiety, escalation and persistence of health concerns. Health anxiety is a mediator in the relationship between Openness to Experience and well-being. It was established that low levels of Agreeableness and Conscientiousness, and high levels of Openness, and Neuroticism, infl uence Internet addiction, which in turn leads to decreased well-being. Furthermore, we established the mediated infl uence of Internet addiction on the tendency for cyberchondria and health anxiety through using the Internet for health information and judgment biases.